Peran teknologi dalam meningkatkan efektivitas pembelajaran di era digital - Octavia, Sandra Gadis (Maliki Interdisciplinary Journal, 2025)
Islamic The advancement of digital technology has significantly transformed the educational landscape, particularly in teaching and learning methods. The use of digital devices such as tablets, learning applications, and online learning management systems enables a more interactive and efficient learning process. This article discusses how technology can enhance learning effectiveness across various educational levels, as well as the challenges faced in its implementation. By examining current literature, this study aims to provide insights into the benefits and limitations of integrating technology in education, focusing on how it can support a flexible, engaging, and accessible learning environment for students. In addition, this article explores the role of technology in facilitating collaborative and project-based learning, which encourages active participation and improves critical thinking skills among students. Addressing the need for teacher training and equitable access to digital resources, this paper emphasizes the importance of strategic planning in implementing educational technology. With the right support, technology can contribute to a modern and inclusive educational experience that meets the evolving needs of today’s learners.